Teachers' Roles in Overcoming Junior High School Students’ Lack of Motivation and Boredom in Learning EFL - Alyani, Pocut Putri Jasmin; Rizqiyani, Kamilah; Banowati, Galih; Khoirunisa, Priyanka Dhevi; Waliyadin, Waliyadin (Institut Agama Islam Negeri Palopo, 2024)
Teachers play a big role in influencing students’ motivation and their way of learning in the classroom. However, teachers also face some challenges in teaching English as a foreign language. One of them is students’ demotivation and boredom. Therefore, this study intends to find out what strategies they use to motivate and reduce students’ boredom in junior high school level at MTsN 13 South Jakarta. Six English teachers of the 7th, 8th, and 9th grades were interviewed. The researcher used qualitative method for this study and semi-structured interview with open-ended questions. To analyze the data, the researchers used thematic analysis. Descriptive design was utilized to elaborate on the findings. The findings showed that the teachers have three ways in overcoming MTsN 13 South Jakarta students’ lack of motivation; by using actions, learning media, and teaching strategies that are suitable for the students.